2014
DOI: 10.4103/2230-8598.137712
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of staphylococcal food poisoning in a nursing hostel, Mysore, Karnataka

Abstract: Objectives: To know the clinical profi le of the students affected due to food poisoning, the possible source of infection and the causative agent for food poisoning. Background: Food-borne diseases due to microbial contamination of food, represent serious threat to the health of millions of people henceforth, we investigated into the outbreak of food poisoning in a nursing hostel of urban Mysore. Materials and Methods: A descriptive study was conducted using semi-structured questionnaire to gather information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Foodborne diseases are increasingly considered a major public health concern globally (Kadariya et al 2014), and is particularly worrisome in developing countries where the majority of foodborne diseases are under reported (Odeyemi, 2016). For example, staphylococcal food poisoning outbreaks have been reported in Switzerland (Johler et al, 2015), United States (CDCP, 2012), Italy (Ercoli et al, 2017;Guidi et al, 2018), Brazil (do Carmo et al, 2003, Australia (Fletcher et al, 2015), Japan (Suzuki et al, 2017), Germany (Johler et al, 2013), India (Basavegowda et al, 2014) etc, while the only reported study on staphylococcal food poisoning outbreak in Africa was reported in Zimbabwe (Gumbo et al, 2015). Interestingly, evidence exists on the practices that favour the proliferation of Staphylococcus aureus in retail ready-to-eat food (Wogu et al, 2011;Farhadian, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Foodborne diseases are increasingly considered a major public health concern globally (Kadariya et al 2014), and is particularly worrisome in developing countries where the majority of foodborne diseases are under reported (Odeyemi, 2016). For example, staphylococcal food poisoning outbreaks have been reported in Switzerland (Johler et al, 2015), United States (CDCP, 2012), Italy (Ercoli et al, 2017;Guidi et al, 2018), Brazil (do Carmo et al, 2003, Australia (Fletcher et al, 2015), Japan (Suzuki et al, 2017), Germany (Johler et al, 2013), India (Basavegowda et al, 2014) etc, while the only reported study on staphylococcal food poisoning outbreak in Africa was reported in Zimbabwe (Gumbo et al, 2015). Interestingly, evidence exists on the practices that favour the proliferation of Staphylococcus aureus in retail ready-to-eat food (Wogu et al, 2011;Farhadian, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Foodborne outbreaks have been occurring for centuries and have continued to torment health authorities. Therefore, in addition to medical examination of the affected individuals, most researchers recommend the implementation of training programs in food safety to form a more comprehensive food control system (Manes et al, 2013;Basavegowda et al, 2014;Djekic et al, 2014;Gumbo et al, 2015). Forecasting foodborne disease outbreaks is a public health strategy that is multi-faceted with socio-economic benefits.…”
Section: Introductionmentioning
confidence: 99%